ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN MENURUNNYA ANGKA KUNJUNGAN KE IGD RSUD RANTAUPRAPAT DIMASA PANDEMI COVID-19 TAHUN 2021 - Nauli Asdam Simbolon (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
Health services are very important for the community, but during the COVID-19 pandemic, people are reluctant to go to health services for fear of contracting the corona virus. The type of research used is Quantitative Research using a Cross-Sectional approach. It was carried out in the Emergency Room at the Rantauprapat Hospital from December 2021 to April 2022. The sample size was calculated by using the minimum sample formula for the unknown population from Lemeshow, the research respondents were 60 respondents, the sampling technique used was consecutive sampling. Variable Knowledge about Covid-19 transmission, Comorbid Covid-19 health conditions, Application of Screening for Patients and Visitors to Emergency Installations and Completeness of Personal Protective Equipment for Emergency Installation Officers related to the decrease in the number of visits to the Emergency Installation of Rantauprapat Hospital during the Covid-19 pandemic in 2021, while the unrelated variable is age. Based on the results of multivariate analysis, it is known that the variable of Personal Protective Equipment for Emergency Installation Officers is associated with a decrease in the number of visits to the ER at Rantauprapat Hospital during the Covid-19 pandemic, based on the p-value 0.003 < 0.05 and based on the Exp(B) value in the test results. Multivariately it is known that the PPE Completeness of Emergency Room Officers has the largest value of 8.248, so it can be concluded that the PPE Completeness of Emergency Room Officers has a chance of 8.248 times causing a decrease in the number of visits to the Emergency Room at Rantauprapat Hospital during the Covid-19 pandemic.